Listeriosis in Rabbits (Oryctolagus cuniculus): A Significant Bacterial Disease with an Emerging Zoonosis - Abd El-Ghany, Wafaa (Journal of Advanced Veterinary Research, 2023)
Rabbit’s rearing becomes one of the most important source of income in many countries world-wide. Rabbit’s meat has many advantageous over any time of meat and it is recommended especially for sick people. Rabbits are susceptible to some important bacterial diseases such as listeriosis which causes severe economic losses. Listeriosis is a disease caused by many species of Listeria which may be environmental saprophytes or sometimes pathogenic for mammals, birds, and humans. Listeria monocytogenes (L. monocytogenes) is the most common cause of illness either in animals or humans. Infection with this bacterium usually occur in animals via ingestion, while in human via handling or consumption of uncooked or under-processed food. Most of signs in rabbits and humans are the same and including septicaemia especially in young, meningoencephalitis, and metritis and fetal mortality in pregnancy. Additionally, human may show the signs of severe febrile gastroenteritis due to food borne illness as well as skin and joint affections. Diagnosis of the disease depends mainly on the traditional methods of isolation and identification along with the recent molecular techniques for detection. Serological diagnosis is of little value. Prevention and control of listeriosis in rabbits are based on cleaning and disinfection of rabbit’s cages, using of specific antibiotic treatment, and application of some natural alternatives such as probiotics and phytobiotics. In human, avoidances of the possible causes of Listeria infection and stressors and administration of a specific drug is the must. Besides, improvement of the quality control measures in processing plants or during handling of food are essential to effectively prevent and control listeriosis associated with food-borne illness. Accordingly, this article focuses on listeriosis in rabbits regarding the pathogenesis and virulence of the causative agent, clinical picture in rabbits, zoonotic importance in human, laboratory diagnosis, and the different strategies used for the prevention and control of the disease.